2001
DOI: 10.1023/a:1011177204593
|View full text |Cite
|
Sign up to set email alerts
|

Western conceptualizations and eastern experience: A cross‐cultural study of traumatic stress reactions among Tibetan refugees in India

Abstract: This study investigated the nature and impact of traumatic experiences among

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0
3

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 25 publications
(30 reference statements)
3
83
0
3
Order By: Relevance
“…The HSCL-25 has proven to be culturally sensitive with samples around the world and has demonstrated sufficient validity and reliability (Fox & Tang, 2000). Similar to Terheggen, Stroebe, and Kleber (2001), we added 10 somatic-items of the Hopkins Symptom Checklist-58 (HSCL-58; Mattson, Williams, Rickels, Lipman, & Uhlenhuth, 1969) that were not redundant to the HSCL-25. This hybrid measure (35 items; hereafter referred to as HSCL) was used to assess a broad range of symptoms of distress.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HSCL-25 has proven to be culturally sensitive with samples around the world and has demonstrated sufficient validity and reliability (Fox & Tang, 2000). Similar to Terheggen, Stroebe, and Kleber (2001), we added 10 somatic-items of the Hopkins Symptom Checklist-58 (HSCL-58; Mattson, Williams, Rickels, Lipman, & Uhlenhuth, 1969) that were not redundant to the HSCL-25. This hybrid measure (35 items; hereafter referred to as HSCL) was used to assess a broad range of symptoms of distress.…”
Section: Methodsmentioning
confidence: 99%
“…Most participants were not fully literate, so measures were administered orally. The Likert scale was demonstrated visually by showing pictures of glasses containing varying amounts of water (Terheggen et al, 2001). Each participant completed the event history, the symptom measures, the Trauma Discourse Exposure interview, and a short sociodemographic form at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…Four studies have examined the traumatic experiences and psychological reactions of adult Tibetan refugees residing in India (Crescenzi et al, 2002;Holtz, 1998;Keller et al, 1997;Terheggen, Stroebe, & Kleber, 2001). Rates of anxiety and depression (based on the Hopkins Symptom Checklist; Derogatis, 1974) varied widely across these studies, ranging from 25% to 70% for anxiety and 14% to 57% for depression.…”
Section: Research On Tibetan Refugees In Indiamentioning
confidence: 99%
“…Holtz (1998) concluded that although torture had long-term psychological effects, social and material support, as well as religious and cultural resources, seemed to protect against psychological distress following trauma. Terheggen et al (2001) reported that witnessing destruction of religious symbols was considered more aversive by Tibetans than imprisonment or torture, highlighting the importance of religious life for this population.…”
Section: Research On Tibetan Refugees In Indiamentioning
confidence: 99%
“…(Machel, 1996) However, not every displaced child experiences terrible atrocities or presents signs of trauma. Several studies have in fact shown that people react to a stressful event in a very individual way, in accordance with the meaning they give to it (Summerfield, 1995;Terheggen et al, 2001). Western views on trauma should therefore not be exported uncritically to other contexts (Bracken & Petty, 1998).…”
Section: Mixed Outcomes For Different Types Of Alternative Educationmentioning
confidence: 99%